2012
DOI: 10.5005/jp-journals-10026-1027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Anaerobic Bacteria in 118 Patients with Deep-space Head and Neck Infections from the People’s University Hospital of Maxillofacial Surgery, Bhopal, India

Abstract: Aim:The aim of this study was to assess the incidence and susceptibility to antibacterial agents of anaerobic strains in 118 patients with head and neck abscesses (31) and cellulitis (87). Materials and methods:In total, 118 pus specimens from 118 consecutive patients with abscesses (31 cases) and cellulitis (87) of the head and neck were evaluated from 2006 to the end of 2011. The patients were admitted to the University Hospital of Maxillofacial Surgery, Bhopal, India, and comprised 76 men and 42 women: Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Other studies have reported a higher incidence of polymicrobial infections. In the study conducted by Kanishka guru et al 8 polymicrobial infection was found in 55.1% of the specimens. According to the study by Shih-Wei Yang et al, Fifty-one out of 89 positive cultures were polymicrobial (57.3%).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies have reported a higher incidence of polymicrobial infections. In the study conducted by Kanishka guru et al 8 polymicrobial infection was found in 55.1% of the specimens. According to the study by Shih-Wei Yang et al, Fifty-one out of 89 positive cultures were polymicrobial (57.3%).…”
Section: Discussionmentioning
confidence: 86%
“…Majority of the previous studies showed a higher rate of culture positivity. In the study conducted by Kanishka guru et al 8 91.5% were culture positive and only 8.5% were culture negative. Another study by Brito TP et al 3 reported 84.5% as culture positive and 14.5% as culture negative.…”
Section: Discussionmentioning
confidence: 87%
“…In relation to the lower head of the external pterygoid muscle the pterygoid venous plexus lies in the fossa. The posterior wall of the maxilla which forms the anterior boundary of this space is paper-thin and pierced by two or three small foramina which transmit the posterior superior alveolar vessels and nerves 4,5 . Uncontrolled and untreated mandibular odontogenic infections rarely spread superiorly to the infratemporal and temporal fossa There is three basic patterns of spread of infection from the masticatory space to temporal space has been identify.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids has been routinely prescribed for the treatment of arthritis and neuritis where as both drainage and antibiotics usage are used for the treatment of nasopharyngeal and infratemporal fossa abscess. If the steroid prescribing to a patient who has infratemporal fossa abscesses, infection will spread to the vital neighboring tissues hence in is required to perform a proper diagnosis for such infection [4][5][6] . To conclude with, infratemporal and temporal fossa infection are rare and is not commonly seen by clinicians and might be easily misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Most (63%) specimens yielding anaerobes yielded more than one and more than 82% of patients with odontogenic sources had specimens that included anaerobes; the most common anaerobes isolated were Gram-positive bacilli (48%), Prevotella (28%), anaerobic Gram-positive cocci (15%), Fusobacterium (13%) and the B. fragilis group (4%) [36]. Most (63%) specimens yielding anaerobes yielded more than one and more than 82% of patients with odontogenic sources had specimens that included anaerobes; the most common anaerobes isolated were Gram-positive bacilli (48%), Prevotella (28%), anaerobic Gram-positive cocci (15%), Fusobacterium (13%) and the B. fragilis group (4%) [36].…”
Section: Head and Neck Space Infectionmentioning
confidence: 99%